‫ﻣﺤﺎﺳﺒﺔ‬‫ﻋﻘﻮد‬ ‫اﻹﻧﺸﺎء‬ ‫ﻣﻦ‬ ‫وﺟﻬﺔ‬ ‫ﻧﻈﺮ‬ ‫اﻟﻨﻈﺎم‬ ‫اﻟﻤﺤﺎﺳﺒﻲ‬ ‫اﻟﻤﺎﻟﻲ‬ ‫و‬ ‫اﻟﻤﻌﺎﻳﻴﺮ‬ ‫اﻟﻤﺤﺎﺳﺒﻴﺔ‬ ‫اﻟﺪوﻟﻴﺔ‬ ‫)‬‫دراﺳﺔ‬‫ﺣﺎﻟﺔ‬ ‫ﻟﺪى‬ ‫ﻣﺆﺳﺴﺔ‬ ‫أﺷﻐﺎل‬ ‫اﻟﺒﻨﺎءسوق اهراس‬ ‫‪‫(‬ - ‬‫ﻋﺮﺑﻴﺔ‫ ﻏﺮاري ‬; ‬‫رﺟﺎء ‫ﺷﻌﻼن ‬ (My University, 2019)
this study aims to address the accounting of construction contracts from the point of view view of the financial accounting system and international accounting standards, considering that the construction contract is one of the most important contracts on which the person depends and represents an important aspect of contracts and transaction between establishments, entrepreneur and employer therefore, this type of construction work must be monitored to determine the procedures implementation and the basis for measuring contract revenues ......................................................... تهدف هذه الدراسة إلى تناول محاسبة عقود البناء من وجهة نظر نظرة على النظام المحاسبي المالي والمعايير المحاسبية الدولية، معتبرا أن عقد البناء من أهم العقود التي يعتمد عليها الشخص وتمثل جانبا هاما من العقود و المعاملات بين المؤسسات ورائد الأعمال وصاحب العمل وبالتالي فإن هذا النوع من يجب مراقبة أعمال البناء لتحديد الإجراءات التنفيذ وأساس قياس إيرادات العقود .